INFLUENCE OF GREEN MANURE ON WATER INFILTRATION AND RESISTANCE TO SOIL PENETRATION UNDER ROTATIONAL CULTURE WITH SUGARCANE AND SWEET SORGHUM - Ferneda, Mirela [UNESP]; Furlan, Felipe Escorce [UNESP]; Qualharello, Tamara [UNESP]; Putti, Fernando Ferrari [UNESP]; Costa, Gustavo Henrique Gravatim; Uribe, Raúl Andres Martinez [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
The hydraulic characteristics of the soil play a very important role in the development of plants, as they act in the storage and transport of water. The objective of the present study was to use green manures in sugarcane plantation reform, evaluating the effects of crotalaria and guandu bean in rotation with sweet sorghum and sugarcane on water infiltration and resistance to soil penetration. The infiltration equations, following the Kostiakov model, were determined from the data resulting from the test with a concentric ring infiltrometer, carried out after the first sugarcane cut, in an experimental area in the city of Cabrália Paulista, SP, Brazil, penetration resistance was measured using the penetrometer. The rotations with green manures provided an increase in the basic infiltration velocity (BIV) and a reduction in penetration resistance. Crotalaria stood out in all studied variables, resulting in a statistically significant increase of 200% in soil BIV and a significant reduction of 15% in penetration resistance. Guandu bean also promoted improvements in soil conditions, however these were less expressive. In this way, it can be stated that the use of crotalaria and guandu bean results in the improvement of the physical characteristics of the soil.
INFLUÊNCIA DA ADUBAÇÃO VERDE NA INFILTRAÇÃO DE ÁGUA E NA RESISTÊNCIA A PENETRAÇÃO DO SOLO SOB CULTIVO ROTACIONADO COM CANA-DE-AÇÚCAR E SORGO SACARINO
Keywords: basic infiltration rate; crop rotation; Crotalária ochraleuca; kostiakov; Saccharum officinarum; Sorghum bicolor L. Moench